2020
DOI: 10.1371/journal.pone.0226926
|View full text |Cite
|
Sign up to set email alerts
|

Still standing: Recent patterns of post-fire conifer refugia in ponderosa pine-dominated forests of the Colorado Front Range

Abstract: Forested fire refugia (trees that survive fires) are important disturbance legacies that provide seed sources for post-fire regeneration. Conifer regeneration has been limited following some recent western fires, particularly in ponderosa pine (Pinus ponderosa) forests. However, the extent, characteristics, and predictability of ponderosa pine fire refugia are largely unknown. Within 23 fires in ponderosa pine-dominated forests of the Colorado Front Range (1996-2013), we evaluated the spatial characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 90 publications
3
18
0
Order By: Relevance
“…Notably, we found that HLI and TPI may help to identify topographic conditions that moderate the influence of broad-scale climate on tree seedlings. Similar terrain variables also help to predict the locations in which trees are most likely to survive fire (Chapman et al 2020;Meigs et al, 2020 Across a range of GCMs and emissions scenarios, we projected that further declines in post-fire seedling densities are likely across much of the SRME. It has been suggested that future warming will reduce conifer seedling establishment and density in many areas, but that increasing temperatures could benefit regeneration at the leading edge (Kemp et al, 2019;Petrie et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, we found that HLI and TPI may help to identify topographic conditions that moderate the influence of broad-scale climate on tree seedlings. Similar terrain variables also help to predict the locations in which trees are most likely to survive fire (Chapman et al 2020;Meigs et al, 2020 Across a range of GCMs and emissions scenarios, we projected that further declines in post-fire seedling densities are likely across much of the SRME. It has been suggested that future warming will reduce conifer seedling establishment and density in many areas, but that increasing temperatures could benefit regeneration at the leading edge (Kemp et al, 2019;Petrie et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Across 23 recent fires in the montane zone of the SRME, 38% of the total area burned is distant from any surviving trees (Chapman et al, 2020). A lack of mature trees also leads to increased daytime temperatures and greater diurnal fluctuations (Davis et al, 2018), with potential impacts on tree seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying burn severity with satellite imagery presents multiple challenges, including spatial variability (e.g., subpixel fire effects), temporal variability (e.g., delayed tree mortality), and the inherent disconnect between remote and ground-based metrics of burn severity (Morgan et al 2014;Dunn and Bailey 2016;Harvey et al 2019). Nevertheless, Landsat-based RdNBR mapping is valuable as a relative indicator of fire-induced change across numerous fire events spanning heterogeneous conditions, particularly when interpreted in the context of field-measured fire effects such as tree mortality (Reilly et al 2017;Chapman et al 2020). We recognize that the fire refugia threshold of 10% BA mortality is subjective, and future studies could test other refugia thresholds or leverage additional spectral information in Landsat imagery (Meddens et al 2016;Collins et al 2019), as well as finer-resolution satellite and aerial imagery (Walker et al 2019;Chapman et al 2020).…”
Section: Uncertainties and Future Researchmentioning
confidence: 99%
“…Nevertheless, Landsat-based RdNBR mapping is valuable as a relative indicator of fire-induced change across numerous fire events spanning heterogeneous conditions, particularly when interpreted in the context of field-measured fire effects such as tree mortality (Reilly et al 2017;Chapman et al 2020). We recognize that the fire refugia threshold of 10% BA mortality is subjective, and future studies could test other refugia thresholds or leverage additional spectral information in Landsat imagery (Meddens et al 2016;Collins et al 2019), as well as finer-resolution satellite and aerial imagery (Walker et al 2019;Chapman et al 2020). Future studies could also integrate field observations to distinguish low-severity from truly unburned refugia (Meddens et al 2016) and quantify the distinctive composition and structure in old forests, particularly in the West Cascades where large, fireresistant Douglas-fir trees are prevalent.…”
Section: Uncertainties and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation